Being stressed in the family or married with work? A literature review and clustering of work-family conflict. Issue 2 (15th October 2021) - Pascucci, Tancredi; Hernández Sánchez, Brizeida; Sánchez García, José Carlos
Abstract : Purpose: Work-family conflict is an important topic which had an evolution, starting from a static definition, where work and family domains were divided, to a more dynamic and complex balance. COVID-19 has influenced society and created a significant distress among families and working activity, and this topic has been characterised by a major interest, considering some old definitions where this balance was considered problematic but not as an enriching opportunity. Design/methodology/approach: The authors used SCOPUS to find all records mentioning work-family conflict, by considering book, article and review, excluding conference paper and considering only records written in English language. After a duplicated and not pertinent record removal, the authors obtained a number of 675 records. The authors considered 437 records from SCOPUS to create a cluster map. Findings: Using SCOPUS and VOSviewer the authors have clustered 5 different areas, which are regrouped in next clusters considering keywords with most co-occurrence and significancy: Work-life balance and burnout gender cluster job stress and performance social and family support job satisfaction. Research limitations/implications: Cluster map is origined only by SCOPUS database. Originality/value: This work aims to find a state of art about this topic, creating hypothesis where this problem has been exacerbated by 2020 due to important society modifications created by COVID-19, where recent evolution of work-family balance has been complicated by papers which come back to consider this balance as problematic.